2023
DOI: 10.1111/anae.16042
|View full text |Cite
|
Sign up to set email alerts
|

Flexible nasal bronchoscopy vs. Airtraq® videolaryngoscopy for awake tracheal intubation: a randomised controlled non‐inferiority study

H. Kamga,
A. Frugier,
M. Boutros
et al.

Abstract: Videolaryngoscopy is a suitable alternative to flexible bronchoscopy to facilitate awake tracheal intubation. The relative effectiveness of these techniques in clinical practice is unknown. We compared flexible nasal bronchoscopy with Airtraq â videolaryngoscopy in patients with an anticipated difficult airway scheduled for awake tracheal intubation. Patients were allocated randomly to flexible nasal bronchoscopy or videolaryngoscopy. All procedures were performed with upper airway regional anaesthesia blockad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…ATI-FB is an ideal intubation technique for dealing with predictably difficult airways. 24 , 25 The patient’s quietness, compliance, and adequate local anesthesia of the airway are critical for the effective completion of this technique. 1 , 26 , 27 The results of this study showed that the differences of epinephrine and norepinephrine at T3 were not statistically significant in the three groups, indicating that the three groups effectively suppressed the stress response of tracheal intubation under local anesthesia combined with appropriate sedatives and analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…ATI-FB is an ideal intubation technique for dealing with predictably difficult airways. 24 , 25 The patient’s quietness, compliance, and adequate local anesthesia of the airway are critical for the effective completion of this technique. 1 , 26 , 27 The results of this study showed that the differences of epinephrine and norepinephrine at T3 were not statistically significant in the three groups, indicating that the three groups effectively suppressed the stress response of tracheal intubation under local anesthesia combined with appropriate sedatives and analgesics.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, although the average outcome is estimated to be negative, in some studies the true outcome may in fact be positive. An examination of the studentized residuals revealed that one study (Kamga H et al, 2023) had a value larger than ±2.6383 and may be a potential outlier in the context of this model. According to the Cook's distances, none of the studies could be considered to be overly influential.…”
Section: Airway Anticipated To Be Normalmentioning
confidence: 98%
“…According to the Q-test, the true results appeared to be heterogeneous (I 2 = 52.5650%). Examination of the studentized residuals revealed that one study (Kamga H et al, 2023) had a higher value of ±2.7729, suggesting it could be a potential outlier in this model. According to…”
Section: First Attempt Successful Intubationmentioning
confidence: 99%
See 2 more Smart Citations